Telemonitoring Interventions in COPD Patients: Overview of Systematic Reviews. (17th January 2020) - Li, Xuanlin; Xie, Yang; Zhao, Hulei; Zhang, Hailong; Yu, Xueqing; Li, Jiansheng
Abstract : Objective . The role of telemonitoring interventions (TIs) for chronic obstructive pulmonary disease (COPD) has been studied in many systematic reviews (SRs) and meta-analyses (MAs), but robust conclusions have not been reached due to wide variations in scopes, qualities, and outcomes. The aim of this overview was to determine the effectiveness of TIs on COPD patients. Methods . PubMed, EMBASE, Web of Science, and Cochrane Library were searched for all reviews on the topic of TI in treating COPD from inception to July 8, 2019, without restrictions on language. According to the inclusion and exclusion criteria, the retrieved literature studies were screened to select SRs and MAs of randomized control trials (RCTs) that evaluated the effects of TIs in COPD patients. The methodological quality of SRs and MAs was assessed with the AMSTAR-2 tool, and the strength of evidence was assessed with the grades of recommendations, assessment, development, and evaluation (GRADE) system for concerned outcomes in terms of mortality, quality of life (SGRQ total scores), exercise capacity (6MWD), and exacerbation-related outcomes (hospitalizations, exacerbation rate, and emergency room visits). Results . Our overview included eight SRs and MAs published in 2011 to 2019, from 95 RCTs involving 10632 participants. After strict evaluation by the AMSTAR-2 tool, 75% of the SRs and MAs in this overview had either low or critically low methodological quality. The effects of TIs for COPD on mortality, quality of life, exercise capacity, and exacerbation-related outcomes are limited, and all of these outcomes scored either low or very low quality of evidence on the GRADE system. Conclusions . There might be insufficient evidence to support the effectiveness of TIs for COPD currently, but the results of this overview should be interpreted dialectically and prudently, and the role of TIs in COPD needs further exploration.